Testing Links of Food-Related Olfactory Perception to Peripheral Ghrelin and Leptin Concentrations - Ginieis, Rachel; Abeywickrema, Sashie; Oey, Indrawati; Peng, Mei (Frontiers in Nutrition, 2022)
The peptide hormones ghrelin and leptin play major roles in the regulation of appetite and food intake. However, the precise effects of these hormones on sensory processing remain a subject of debate, particularly with food related stimuli and its small body of evidence. Here, we test for relationships between ghrelin and leptin levels against olfactory performance with multiple food-related odours. Specifically, a total of 94 Caucasian males were tested for their supra-threshold sensitivity (i.e., d′), intensity, and valence perception to three odour compounds (i.e., vanilla, potato, and dairy odours). These sensory data were then analysed against peripheral ghrelin and leptin levels, both assessed in plasma samples. Participants’ body adiposity measures were also obtained. Results lent strong support to one of our original hypotheses, with ghrelin levels being positively correlated to the supra-threshold sensitivity of the dairy odour, (r = 0.241, p = 0.020), and intensity ratings to most of the food odours tested [dairy (r = 0.216, p = 0.037) and vanilla (r = 0.241, p = 0.020)]. By contrast, peripheral leptin levels were not significantly linked to any of the olfactory measures (p > 0.05). These relationships remained similar after controlling for variabilities of adiposity measures. The present study brings novel insights by identifying positive links between supra-threshold olfactory perception and ghrelin. This new knowledge is highly relevant for future research linking olfactory shifts to hormonal dysregulation and obesity.